Pendampingan Perencanaan - Talitha Zhafira; Ahmad Hakim Bintang Kuncoro; Anik Kustirini; Mentari S Sitorus (Institut Nalanda, 2023)
Sidorejo Village, Bandongan sub-district, Magelang Regency, according to data from the Agriculture Service, has beef cattle which continues to increase every year. This made the village community continue to improve cattle farming. A good farm must have a conceptual and sustainable building infrastructure. The partner's problem with community service is that they want to plan a modern farm. The community service team is here to provide assistance and direction so that the site plans and enclosures are divided according to their respective functions. In the future the location of this farm will be used as a container for fermented cattle feed from straw by utilizing the surrounding straw waste. The result of the assistance from the PKM team is increased understanding and information on land layout and space placement in accordance with the concept of modern cattle farming. This can be seen from the increase in the percentage of pre-test and post-test from 35% to 65%.